REACTIVE AMYLOID A PROTEIN AMYLOIDOSIS IN THE SETTING OF INFECTIVE ENDOCARDITIS MANIFESTING AS BILATERAL ORBITOPATHY AND CHOROIDOPATHY. Issue Volume 16:Issues 6(2022) (November 2022) - Carrera, William; Rosco, Michael G.; Safo, Myra; Peng, Michelle Yun; Ng, Caleb; Agarwal, Anita
Abstract : Orbital AA amyloidosis can induce a local inflammatory response, manifesting as orbital swelling, papillitis, posterior scleritis, choroiditis, and exudative retinal detachment. Choriocapillaris vasoocclusion with reactive inflammation to the presence of amyloid fibrils likely underlies this presentation. Abstract : Purpose: To describe a case of amyloid A protein amyloidosis that produced an orbital inflammatory response with a novel presentation. Methods: Case report. Results: A 24-year-old Caucasian women with a history of intravenous heroin use was hospitalized for tricuspid valve endocarditis and methicillin-resistant Staphylococcus aureus bacteremia, as well as acute renal failure. She received hemodialysis and intravenous daptomycin and had negative blood cultures for 3 weeks, when she developed sudden bilateral orbital swelling and blurred vision. Visual acuity was 20/200 in the right eye and 20/400 in the left eye. Examination revealed proptosis, conjunctival chemosis and desiccation, optic disk swelling, creamy choroidal infiltrates, and inferiorly located exudative retinal detachments in both eyes. Multimodal imaging demonstrated thickening of the sclera, choroid, and choriocapillaris as well as outer retinal disruption, subretinal fluid, and deposits of hyperfluorescent debris within the choriocapillaris, outer retina, and vitreous. Oral prednisone at 60 mg per day resolved the choroidal infiltrates and exudative detachments. Persistent nephrotic syndrome called for a renal biopsy, which demonstrated amyloid A protein amyloidosis. Conclusion: Orbital and choroidal Amyloid A protein amyloidosis can induce a local inflammatory response manifesting as orbital swelling, papillitis, posterior scleritis, choroiditis, and exudative retinal detachment, which responds to steroid therapy. The underlying pathology is likely a reactive inflammatory, vasoocclusive process involving the choriocapillaris and orbital vasculature to the presence of amyloid fibrils.